Metal oxides and polysaccharides: an efficient hybrid association for materials chemistry. Issue 1 (1st October 2014) - Boury, B.; Plumejeau, S.
Abstract : Polysaccharides are ideal templates for greening the synthesis of metal oxides by biotemplating and bio-replication. Abstract : Metal oxides and polysaccharides in nature and in laboratories: limits and aims of the review. Part 1: Different ways to associate metal oxides and polysaccharides. Part 2: Controlled growth of metal oxide nanoparticles throughout polysaccharide fibers. Part 3: Biotemplating and bio-replication on the micro- to nanoscale. Part 4: Chemical transformation of polysaccharide fibers by mineralisation. Perspectives and concluding remarks. Biopolymers and inorganic minerals are often associated in nature, and living organisms benefit from these materials with a sophisticated and hierarchical architecture. Inspired by nature, chemists have tried to extend these combinations by associating natural polymers with inorganic materials that do not occur naturally in living organisms. In this review, we propose to focus only on research conducted on the association between polysaccharides and metal oxides. Over the last 10–15 years, substantial research has been focused on finding ways to combine these two types of materials, with the goal of mastering the morphology, porosity, composition and structure of the hybrid materials (metal oxide@polysaccharide) or pure metal oxides obtained after polysaccharide elimination. There are many possibilities for interactions between metal cations and the chemical functionality of the carbohydrate, thus allowing different approaches, as the structure and functionality of the polysaccharide are of major importance. Because of the sophisticated architecture that can be achieved on the one hand, and the potential sustainable use of these biopolymers (a green approach) on the other hand, these material elaboration processes offer a unique way for chemists to prepare functional hybrid materials and metal oxides ( e.g. luminescent materials, catalysts, absorbent materials, magnetic composites, anode and photocatalyst materials). To be as comprehensive as possible, this review is limited to some natural polysaccharides. After contextualisation, we successively considered metal oxide growth control by biotemplating, the replication of raw and refined polysaccharide templates, ending with a discussion of the most recent approaches like mineralisation.